Analysis of the marketing environment of the organization on the basis of the cognitive approach - T. Y. Shpakova (Путеводитель предпринимателя)
This article describes one of the most significant factor in the development of the organization - marketing environment. Concretized the concept of process mechanism. Particular attention is paid to the construction process of analyzing the marketing environment in the implementation of innovations in terms of the cognitive approach to the buyers in making purchasing decisions.